Experimental study on the prediction of rockburst hazards induced by dynamic structural plane shearing in deeply buried hard rock tunnels. (July 2016) - Meng, Fanzhen; Zhou, Hui; Wang, Zaiquan; Zhang, Liming; Kong, Liang; Li, Shaojun; Zhang, Chuanqing
Abstract: To investigate methods for predicting bursts induced by the shear failure of structural planes in the deeply buried hard rock tunnels, shear tests were performed under various normal stresses on completely occlusive granite joints that were created via tension splitting. In these experiments, stress drops resulting from shear off of asperities on the surface of granite rigid structural plane, which can trigger a fault-slip rockburst, were reproduced, and the acoustic emissions (AEs) were monitored during shearing. The AE characteristics were analysed, and a method based on the AE b -value was developed to predict stress drops and the fault-slip rockbursts induced by the stress drops. The b -value continuously decreased before the stress drop and dropped to approximately 0.8 or less at the point of the violent post-peak shear stress drop. Moreover, the b -value tended to decrease to a relative minimum during the stick-slip period when the energy increased sharply if the energy rate was greater than 10 4, and a lower b -value was associated with a higher rockburst probability and intensity. The b -value generally decreased as the normal stress increased, which increased the risk of rockburst induced by the dynamic shear failure of granite joints. Moreover, the static and dynamic shear failure of the joints was easily distinguished when the b -value was used as a predictor. Highlights: Shear tests were performed on completely interlocked rigid granite structural planes. Acoustic emission (AE) was monitored during the shear failure of the joints. Rockbursts can be induced by violent post-peak stress drops or unstable stick-slip. Rockbursts caused by dynamic shear failure can be predicted from the AE b -value. The b -value tends to decrease as the normal stress increases.